2019
DOI: 10.1111/ipd.12491
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion in children and adolescents with Down syndrome: A systematic review and meta‐analysis

Abstract: Background Previous studies have shown a high prevalence of malocclusion in people with Down syndrome (DS) compared to individuals without DS, but no systematic review to summarize the evidence on this topic has been performed thus far. Aim To evaluate whether children/adolescents with DS are more affected by malocclusion than those without DS. Design A search was performed in seven electronic databases. The quality of the included studies was assessed using the Newcastle‐Ottawa Scale. The strength of the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
4
25
0
2
Order By: Relevance
“…The findings of the study have supported the outcomes of the current study and have mentioned that most children need orthodontic treatment. Moreover, work completed by Doriguetto et al has also supported the outcomes of the current study [14]. The present study aimed to identify malocclusion among children and adolescents suffering from Down syndrome.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the study have supported the outcomes of the current study and have mentioned that most children need orthodontic treatment. Moreover, work completed by Doriguetto et al has also supported the outcomes of the current study [14]. The present study aimed to identify malocclusion among children and adolescents suffering from Down syndrome.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the previously published systematic review, findings indicated that malocclusion was more prevalent among children suffering from Down syndrome; therefore, orthodontic treatment needs are also higher among children suffering from Down syndrome. The current study is based on primary data; therefore, the study conducted by Doriguetto et al appropriately verifies the outcomes of the current study [14].…”
Section: Discussionsupporting
confidence: 59%
“…A systematic review and meta‐analysis demonstrated that children and adolescents with DS have a higher prevalence of malocclusions compared with their peers without DS (Doriguêtto et al . 2019). In our study, over half (58.62%) of children and young people with DS showed malocclusions, as reported in the literature (Abdul Rahim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Low muscle tone in the lips and tongue, as well as difficulties with chewing, swallowing, speech and other orofacial functions, may affect feeding ability during infancy [10]. An underdeveloped maxilla, hypodontia, narrow airways, hypotonic muscles and tongue protrusion can increase the development of malocclusions [11][12][13][14]. The risk of obstructive sleep apnoea syndrome and respiratory tract infections is high in children with DS compared to typically developing children [15].…”
Section: Introductionmentioning
confidence: 99%